Youtube dan Panggung Politik Wakil Walikota Surabaya Armuji - Widyawati, Agustina; Dhimam Abror; Nur’annafi Farni Syam Maella (Journal Communication Specialist, 2023)
This research is to critically determine the extent to which the use of YouTube as a media for political campaigns by the Deputy Mayor of Surabaya, Armuji. Since 2010, Internet and new media usage become standart for political practice by political actors. Causes of new media usage become popular are the platform that converge text, audio, and video. Not only that, new media also offer two way communication. Compared to regular press release, YouTubecould properly disseminate crucial information more personally or dialogically on responding the constituent. Not only international and national politicians, regional/local political actors are increasingly using social media as a political communication channel. Deputy Mayor of Surabaya Armuji chose to focus on using the YouTube channel as his campaign tool. Using Teun A. Van Dijk’s Critical Discourse Analysis model, researchers examined Armuji’s Youtube Channel in the #CakJiPodcast program entitled “Bahas Suroboyo dan Persebaya Bareng Pak Dahlan Iskan.” In terms of critical analysis of political news texts based on the van dijk tool, it was found that Deputy Mayor of Surabaya Armuji used the CakJi Podcast broadcast as a form of digital political campaigning. Although not openly in the form of political speeches or invitations to vote/vote. However, from the dialogue that flowed between him and the speakers, a positive image of himself emerged and strengthened.